2023
DOI: 10.1021/jacs.2c13527
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Ligand Passivation as the Origin of Near-Unity Emission Quantum Yields in CsPbBr3 Nanocrystals

Abstract: Key features of syntheses, involving the quaternary ammonium passivation of CsPbBr3 nanocrystals (NCs), include stable, reproducible, and large (often near-unity) emission quantum yields (QYs). The archetypical example involves didodecyl dimethyl ammonium (DDDMA+)-passivated CsPbBr3 NCs where robust QYs stem from interactions between DDDMA+ and NC surfaces. Despite widespread adoption of this synthesis, specific ligand–NC surface interactions responsible for large DDDMA+-passivated NC QYs have not been fully e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…Quaternary ammonium passivated CsPbBr 3 NCs were synthesized via literature procedures. , Benzoyl bromide was introduced to premade Cs–Pb-oleate to trigger NC growth. Particles were subsequently passivated with didodecyl dimethylammonium bromide (DDDMABr), washed with ethyl acetate, and redispersed in toluene.…”
Section: Resultsmentioning
confidence: 99%
“…Quaternary ammonium passivated CsPbBr 3 NCs were synthesized via literature procedures. , Benzoyl bromide was introduced to premade Cs–Pb-oleate to trigger NC growth. Particles were subsequently passivated with didodecyl dimethylammonium bromide (DDDMABr), washed with ethyl acetate, and redispersed in toluene.…”
Section: Resultsmentioning
confidence: 99%
“…TlPbI 3 also exhibits a sensitive photoresponse with a photocurrent/dark current ratio of approximately 80:1 . Moreover, CsPbBr 3 and (NH 4 ) 3 Bi 2 I 9 perovskites demonstrate impressive sensitivity as X-ray detectors. Peng et al synthesized colloidal CsPbBr 3 nanocrystals with a high photoluminescence quantum yield (PLQY) of 93.8 ± 1.3%. ,, Sun et al found that doping 2.8% Ni into the CsPbCl 2.4 Br 0.6 lattice can significantly increase the PLQY from 1.2 to 92.0%. , Additionally, the field of perovskite lasing has underwent rapid development since the discovery of ultralow-threshold room-temperature amplified spontaneous emission (ASE) and lasing from CH 3 NH 3 PbX 3 . …”
Section: Introductionmentioning
confidence: 99%
“…26−28 Peng et al synthesized colloidal CsPbBr 3 nanocrystals with a high photoluminescence quantum yield (PLQY) of 93.8 ± 1.3%. 10,16,29 Sun et al found that doping 2.8% Ni into the CsPbCl 2.4 Br 0.6 lattice can significantly increase the PLQY from 1.2 to 92.0%. 30,31 Additionally, the field of perovskite lasing has underwent rapid development since the discovery of ultralow-threshold room-temperature amplified s p o n t a n e o u s e m i s s i o n ( A S E ) a n d l a s i n g f r o m CH 3 NH 3 PbX 3 .…”
Section: Introductionmentioning
confidence: 99%
“…[4,[22][23][24] Of these, didodecyldimethylammonium halide (DDAX, X = F, Cl, Br, I) ligands have been successfully demonstrated to increase the efficiency of LEDs by passivating the PNC surface. [25][26][27] On the other hand, a B-site engineering strategy with divalent metal dopant cations has successfully been used to control B-site vacancies stabilize surface, and reduce the defect density of PNCs, where the divalent metal ions are known to strengthen the bonding with surface ligands and prevent the desorption of organic ligands. [28,29] In particular, the incorporation of small B-site cations such as Cd 2+ has been shown as a strategy to better accommodate the relatively large quaternary ammonium ligands by partially distorting the near-surface [MX 6 ] [4]− octahedra to render large-sized A-site vacancies, providing us with an interesting example of how the A-and B-site species can effectively influence each other during passivation.…”
Section: Introductionmentioning
confidence: 99%
“…[ 4,22–24 ] Of these, didodecyldimethylammonium halide (DDAX, X = F, Cl, Br, I) ligands have been successfully demonstrated to increase the efficiency of LEDs by passivating the PNC surface. [ 25–27 ]…”
Section: Introductionmentioning
confidence: 99%